SISTEM INFORMASI PERHITUNGAN LEMBUR DAN INSENTIF UNTUK MENDUKUNG TRANSPARANSI KOMPENSASI KARYAWAN PADA PT PUPUK SRIWIDJAJA PALEMBANG - Putri Delarani Azzahra; Muhamad Son Muarie (CV. Denasya Smart Publisher, 2025)
The rapid development of information technology requires companies to manage data and business processes effectively, including employee compensation management. PT Pupuk Sriwidjaja Palembang, as a state-owned enterprise with a large number of employees, requires an information system that can support accurate, efficient, and transparent overtime and incentive calculations. The background of this study is the existence of semi-manual processes in the recapitulation and verification of overtime and incentive data, which may lead to errors and delays in payment. The methods used in this internship study include observation, interviews, documentation, and literature review, as well as system analysis using the Rapid Application Development (RAD) method. The results of the discussion indicate that an integrated overtime and incentive calculation information system, connected with attendance, personnel, and financial systems, is able to improve process efficiency, calculation accuracy, and support transparency in employee compensation. However, further system development is still needed to reduce manual processes and enhance real-time information access for employees.